P-079: IL10R inhibition reprograms tumor-associated macrophages and reverses drug resistance in Multiple Myeloma - Sun, Jennifer; Muz, Barbara; Alhallak, Kinan; Park, Chaelee; Lubben, Berit; Fiala, Mark; Vij, Ravi; Azab, Abdel Kareem (Clinical lymphoma, myeloma and leukemia, 2021)
Multiple myeloma (MM) is a cancer of plasma cells within the bone marrow (BM) and remains to be incurable. Tumor-associated macrophages (TAMs) are a major immunosuppressive component in the tumor microenvironment and display the pro-tumor M2 phenotype, supporting tumor proliferation, survival, and drug resistance. Targeting TAMs to block their pro-tumor functions represent a promising class of cancer immunotherapy. IL10 is a key immunosuppressive cytokine that leads to recruitment and development of TAMs. In this study, we investigate the role of IL10 in MM TAM development, and hypothesize that inhibition of IL10/IL10R signaling in TAMs will reprogram them for MM killing and overcome drug resistance. Macrophage (MPP) polarization to M1 (CD80+) or M2 (CD163+) is determined by antibody staining and flow cytometry. In vitro and ex vivo studies were carried out in our lab’s proprietary 3D tissue-engineered BM model (3DTEBM). First, we compared TAM M2/M1 ratio as well as IL10 cytokine levels in the BM of healthy and MM subjects. To study the role of IL10 in TAM development, we co-cultured MΦ with increasing MM cells or rhIL10 in the 3DTEBM for 3 days and analyzed the resulting M2/M1 ratio. To determine the effect of IL10R inhibition, MM and MΦ co-cultures, or unsorted patient BM were treated with or without 5ug/ml α-IL10R monoclonal antibody (mAb), and TAM phenotype was analyzed after 3 days. Additionally, humanized huCD34-NCG mice were inoculated with MM cells and treated with α-IL10R mAb 3 times/week for 2 weeks; mice femurs were flushed and BM cells were analyzed for TAM phenotype. Finally, we investigated α-IL10R mAb as combination treatment with chemotherapy in MM-GFP and MΦ co-cultures; MM survival was determined by count of GFP+ cells and apoptosis was determined by Annexin/PI staining with flow cytometry. Compared to healthy subjects, M2/M1 ratio in MM patient TAMs were 3-fold higher, and BM IL10 level was 3.8-fold higher. Additionally, increasing MM cell ratio in co-cultures induced TAM polarization to M2, and was contributed by IL10. Importantly, α-IL10R mAb was able to reverse MM induced M2 TAM phenotype in vitro, ex vivo, and in vivo. Moreover, the presence of TAMs resulted in significant MM proliferation and chemotherapy resistance toward lenalidomide and dexamethasone. However, combination treatment with α-IL10R mAb completely reversed the drug resistance and abrogated cancer cells in vitro, partially due to induction of apoptosis in MM cells. In summary, we have shown that MM induced M2 polarization of TAMs in an IL-10 dependent fashion, and disruption of IL10/IL10R signaling reversed M2 phenotype in TAMs, and overcame TAM-supported drug resistance. Future studies are warranted to examine mechanism behind overcoming drug resistance as well as the effect of α-IL10R immunotherapy in vivo and in patients.